2020
DOI: 10.1002/dc.24633
|View full text |Cite
|
Sign up to set email alerts
|

Is cervical cytology testing as a part of co‐test unnecessary for HPV 16/18‐infected women? A retrospective cohort study of 1647 women

Abstract: BackgroundWe aimed to present the biopsy results of women with HPV 16/18 infection and investigate whether cytology is necessary as a part of routine cervical cancer screening in women with HPV 16/18.MethodsThis is a retrospective cohort study conducted on 1647 patients between the ages of 30 and 65 years with HPV 16/18 undergoing colposcopy‐guided biopsy at a tertiary gynecological cancer center between January‐2016 and January‐2019. We compared the preinvasive lesion rates and the invasive cervical cancer ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
1
5
1
Order By: Relevance
“…Even though we did not detect any cases of invasive cervical carcinoma, other groups found invasive cervical carcinoma in up to 0.5% of the women [43,44,46]. Interestingly, Giray et al observed that the rate of invasive cancer did not differ significantly between women with normal and abnormal cytology in HPV 16/18 positive women (0.5% vs. 1.5%, p = 0.082) and concluded that Pap testing could be unnecessary in HPV 16/18 positive women who will undergo colposcopy-guided biopsy to diagnose invasive cervical cancer [44].…”
Section: Histopathological Resultscontrasting
confidence: 97%
See 2 more Smart Citations
“…Even though we did not detect any cases of invasive cervical carcinoma, other groups found invasive cervical carcinoma in up to 0.5% of the women [43,44,46]. Interestingly, Giray et al observed that the rate of invasive cancer did not differ significantly between women with normal and abnormal cytology in HPV 16/18 positive women (0.5% vs. 1.5%, p = 0.082) and concluded that Pap testing could be unnecessary in HPV 16/18 positive women who will undergo colposcopy-guided biopsy to diagnose invasive cervical cancer [44].…”
Section: Histopathological Resultscontrasting
confidence: 97%
“…While we observed only very few CIN 1 cases (three in total, all of them other hrHPV positive), prevalence of CIN 1 is reported as high as 21.6% in HPV 16/18 positive women [ 44 ] and 23.9% for other hrHPV positive, cytology negative women [ 43 ]. The comparably low number of CIN 1 cases in our study might at least be partially explained by referral for colposcopy only in case of a persistently positive HPV test after 12 months.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Comparison with existing research can offer valuable insights into HPV genotypes' epidemiology and their associated factors. However, direct comparisons can sometimes pose challenges due to the varying population characteristics, HPV testing methodologies, and statistical analysis methods employed across different studies [13,14]. Large-scale, multicenter studies would serve to substantiate our ndings and establish stronger associations.…”
Section: Discussionmentioning
confidence: 99%
“…The Pap test refers to the cancer prevention method that involves a specific and laborintensive analysis of cytological arrangements to trace possibly cancerous cells from the external and internal cervix surface [16]. While looking for abnormal cells, a cytopathologist must examine various microscopic regions [17].…”
Section: Introductionmentioning
confidence: 99%